THE “JUSTICE INDEX” IS A STEP TOWARDS THE IMPLEMENTATION OF THE GLOBAL GOAL 16 OF THE U.N. AGENDA - E. Alekseevskaya; L. Treskina (BRICS Law Journal, 2018)
This paper proposes a method for measuring sustainable development as a means of the implementation of the Global Goal 16 of the United Nations Agenda. This method is the primary attempt to quantify the quality of the rules of the judiciary and access to a court in order to monitor sustainable development in the area of justice. In the recent years, the U.N. drew attention to the fact that qualitative changes should be evaluated through quantitative indicators.The authors’ methodology is based on the fair trial standard formulated by the European Court of Human Rights based on the interpretation of Article 6 of the Convention for the Protection of Human Rights and Fundamental Freedoms, as well as the public services standard of the Russian Federation. This indexing method helps to assess the current level of legal guarantees in the rules of legal proceedings and draft legislation, and to establish their compliance with the fair trial principles. Indexing the access to justice has another positive effect – it helps to monitor the local situations and every level of the judicial system.Putting this method into practice will encourage avoidance of the adoption of bills that might reduce the level of legal guarantees and will assist attempts to monitor its dynamics. It could promote the introduction of effective procedures and better access to court, ensure the improved accountability of all public justice institutions at all levels and support overall societal wellbeing.